CARTOON MOVIE CLIPS: MEDIA INOVATIF DALAM MENINGKATKAN KOSAKATA BAHASA INGGRIS SISWA SDN 5 SUWAWA - Danial, Haris; Ngadi, Nurlin Amelia Chelsi; Hadjaratie, Noerja Fadhilla (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2025)
This study investigates the effectiveness of using cartoon movie clips to enhance students' vocabulary mastery at SDN 5 Suwawa. The research employed a pre-experimental design with one group pre-test and post-test involving 31 fifth-grade students. The treatment was conducted over six sessions, where students were taught vocabulary through animated clips combined with games and role-playing strategies. The data were collected through vocabulary tests administered before and after the treatment. The results showed a significant improvement in students’ vocabulary scores, with the average score increasing from 32.93 in the pre-test to 65.5 in the post-test. Statistical analysis using a t-test indicated that the calculated t-value (-26.7) was lower than the critical value (-1.70), leading to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1). These findings support the conclusion that cartoon movie clips are effective in improving vocabulary mastery. Moreover, cartoon clips provided a visual and auditory learning experience that made vocabulary learning more engaging and enjoyable. However, challenges such as potential distractions and limited generalizability were also identified.